PENGARUH METODE PEMBELAJARAN EKLEKTIK TERHADAP HASIL BELAJAR BAHASA ARAB SISWA - Raswan Raswan (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2018)
This research is aimed to know the effect of learning method’s towards Arabic Achievement of the Fifth Grade Students of Islamic Elementary School Pembangunan Islamic State University Sharif Hidayatullah Jakarta 2009/2010. The research questions were: is there any difference in Arabic learning achievement as a whole between a group of students who have been given intiqâiyyah methods and another group of students who have been given conventional methods. This research was an experimental study using randomized control group design. The influencing factorial variable are learning methods on Arabic. The Arabic learning achievement was used to know the students’ skill or capability Arabic learning. In experimental class, intiqâiyyah methods as experiment methods, and conventional methods as control methods. This research concluded that there was any difference between students Arabic achievements of group of students who have been given intiqâiyyah methods and group of students who have been given conventional methods.